2007
DOI: 10.1007/s00210-007-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of inwardly rectifying Kir2.x potassium channels by β3-adrenoceptors is mediated via different signaling pathways with a predominant role of PKC for Kir2.1 and of PKA for Kir2.2

Abstract: beta(3)-adrenoceptors have recently been shown to induce a complex modulation of intracellular signaling pathways including cyclic guanine monophosphate, cyclic adenosine monophosphate, nitric oxide, and protein kinases A and C. They are expressed in a broad variety of tissues including the myocardium, vascular smooth muscle, and endothelium. In those tissues, resting membrane potential is controlled mainly by inwardly rectifying potassium channels of the Kir2 family namely, Kir2.1 in the vascular smooth muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Previous studies of the β-adrenergic stimulation effects on I K1 have reported controversial results. Facilitation of I K1 by isoproterenol treatment was reported by Trombe et al [26], Gadsby et al [7] and Scherer et al [24], whereas reduction of I K1 by isoproterenol was reported by Koumi et al [14], Wischmeyer et al [29], and Fauconnier et al [6]. The above experiments were all conducted using traditional V-clamp technique.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies of the β-adrenergic stimulation effects on I K1 have reported controversial results. Facilitation of I K1 by isoproterenol treatment was reported by Trombe et al [26], Gadsby et al [7] and Scherer et al [24], whereas reduction of I K1 by isoproterenol was reported by Koumi et al [14], Wischmeyer et al [29], and Fauconnier et al [6]. The above experiments were all conducted using traditional V-clamp technique.…”
Section: Discussionmentioning
confidence: 93%
“…3B) shows 5-fold growth of the inward current without a significant change in the reversal potential and without an increase in the outward current over nearly 2 h. Similar results were obtained from all cells injected with AmqKirB although the rate of increase of inward current varied from cell-to-cell. Run-up has been reported for vertebrate Kir2.1 and Kir2.2 currents and may be explained by PKA activity whereas these currents were downregulated by activation of PKC (Fakler et al, 1994;Scherer et al, 2007;Zitron et al, 2004). ] o , caused the reversal potentials for AmqKir currents to shift in accordance with the E K .…”
Section: Electrophysiological Propertiesmentioning
confidence: 88%
“…Currents through K IR 2.2 channels are increased by activated PKA through phosphorylation of S430 (1653). Additional studies have shown that activation of β 3 -adrenoreceptors increases currents through K IR 2.1 and K IR 2.2 channels (1259). For K IR 2.1, this appears to involve PKC, for K IR 2.2, cAMP and PKA-mediated activation (1259).…”
Section: Kir Channelsmentioning
confidence: 99%